Pelatihan Usaha Tani Microgreens bagi Ibu Rumah Tangga - Reny Sukmawani; Neneng Kartika Rini; Inda Asri Supiati; Ema Hilma Meilani; Amalia Nur Milla; Endang Tri Astutiningsih (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
This Community Service is entitled Microgreens Farming Business Training for Housewives in Sukabumi. The empowerment of housewives is intended to produce the potential of housewives, in addition to being able to carry out domestic or domestic duties. Housewives are also able to be active and productive in public activities and economic activities. Microgreens are vegetable seeds that are harvested very young, 7-14 days after germinating and young leaves appear. The method used in this service is the training method; namely, before carrying out direct practice, participants understand through theory first. The training participants were housewives from several women's organizations in Sukabumi. This community service is the acquisition of skills of housewives in farming microgreens and the increasing role of housewives in family welfare through the provision of healthy vegetables for the family.